Numerical simulation of the aerodynamics of a cycloidal rotor in flight - Dekterev, Aleksandr Anatol′yevich; Dekterev, Artem Aleksandrovich; Dekterev, Dmitriy Aleksandrovich; Kretinin, Vasiliy Vasil′yevich; Sentyabov, Andrey Vasil′yevich; Filimonov, Sergey Anatol′yevich; Finnikov, Konstantin Andreyevich (Computational Continuum Mechanics, 2025)
The paper presents numerical simulation of the aerodynamics of a cycloidal rotor in various modes. The cycloidal rotor is a rotor consisting of several blades parallel to its axis and capable of changing their pitch angle as it rotates. The rotor’s aerodynamics is modeled in the formulation of a three-dimensional turbulent incompressible air flow. The numerical model is based on the computational fluid dynamics methods, in particular, the computational domain is discretized by the control volume method, and the motion of blades is modeled using the sliding mesh method. The results of test calculations are in good agreement with the experimental data. It is shown that, during rotation, the blade passes two parts of rotor thrust generation, most of which falls on the lower half of the cycle. To find the rotor characteristics under flight conditions, calculations were performed for the flow around a single rotor by the incident flow with varying velocity and direction. It was found that the vertical component of the force increases with increasing rotor descent speed. Under a horizontal flow, the power and, accordingly, the rotor efficiency change greatly. The calculations performed for two rotors in the incident flow show that their parameters change significantly and in opposite directions with increasing flow velocity. In this case, the torque on the front rotor decreases with increasing flow velocity, and on the rear rotor it increases. At a moderate incident flow velocity, the rotors have almost no effect on each other. As the incident flow velocity increases, rotor control requires deflection of the air jet thrown off by the rotors, as a result of which the jet created by the front rotor falls on the rear rotor, which leads to deterioration of its characteristics.